2003
DOI: 10.1046/j.1524-475x.2003.11407.x
|View full text |Cite
|
Sign up to set email alerts
|

Development of a reconstructed human skin model for angiogenesis

Abstract: We have previously shown that reconstructed human skin engineered from autologous keratinocytes, fibroblasts, and sterilized donor allodermis stimulates angiogenesis within 5-7 days when placed on well-vascularized wound beds in nude mice. When this reconstructed skin was used clinically in more demanding wound beds, some grafts were lost, possibly due to delayed vascularization. As this reconstructed skin lacks any endothelial cells, our aim in this study was to develop an angiogenic reconstructed skin model … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
71
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 109 publications
(73 citation statements)
references
References 23 publications
1
71
0
Order By: Relevance
“…Fibroblasts play an important role in organizing the clot, which includes the secretion of extracellular matrix and the promotion of angiogenesis. 14,15 To our knowledge, bi-layered prevascularized skin grafts so far have been only engineered based on the so-called ''self-assembly approach,'' [16][17][18] collagenbased scaffolds, 19,20 de-cellularized donor dermis, 21 or use of a de-cellularized porcine jejunal segment as suggested by Groeber et al 22 All of these methods are characterized by specific shortcomings: The self-assembly approach takes approximately 6 weeks to form a prevascularized neo-dermis, which is a significantly longer timeframe than our employed method. Collagen-based scaffolds, de-cellularized donor dermis, or xenogenous templates cannot offer a complete autologous approach; drawbacks such as transmission of infectious diseases, allergic reactions, or intricate experimental setup have to be taken into account as a possible future issue regarding human implementation.…”
Section: Discussionmentioning
confidence: 99%
“…Fibroblasts play an important role in organizing the clot, which includes the secretion of extracellular matrix and the promotion of angiogenesis. 14,15 To our knowledge, bi-layered prevascularized skin grafts so far have been only engineered based on the so-called ''self-assembly approach,'' [16][17][18] collagenbased scaffolds, 19,20 de-cellularized donor dermis, 21 or use of a de-cellularized porcine jejunal segment as suggested by Groeber et al 22 All of these methods are characterized by specific shortcomings: The self-assembly approach takes approximately 6 weeks to form a prevascularized neo-dermis, which is a significantly longer timeframe than our employed method. Collagen-based scaffolds, de-cellularized donor dermis, or xenogenous templates cannot offer a complete autologous approach; drawbacks such as transmission of infectious diseases, allergic reactions, or intricate experimental setup have to be taken into account as a possible future issue regarding human implementation.…”
Section: Discussionmentioning
confidence: 99%
“…Studies with HDMEC have shown that it may take up to 6 weeks to prepare therapeutic amounts for STE. 11 Our own experience with AB-BOEC also indicates that it may take several weeks to expand them to a clinically useful number. An important advantage of the latter compared to HDMEC is that the total amount of cells that can be generated is larger, so that excess cells may be cryopreserved for later use in the same patient.…”
Section: Pluripotent Progenitor Cellsmentioning
confidence: 96%
“…27 Further refinement of the culture protocol has led to the development of serum-free culture techniques, making these cells safer for potential clinical use in STE. 28 However, despite optimization of techniques to obtain HDMEC, the limited yield requires time-consuming culture expansion (up to 6 weeks) and contamination with fibroblasts remains a challenging problem, 11,25 which currently impedes their use in a clinical setting. Although Nö r et al succeeded in creating functional vessels in a subcutaneous pocket when combining HDMEC with matrigel, Supp et al did not demonstrate functional connection to the host vasculature in a skin substitute.…”
Section: Mature Ecmentioning
confidence: 99%
See 2 more Smart Citations